Morphological And Biochemical Responses Of Saccharum Spontaneum L. Accessions To Drought Stress - Aminatun Munawarti; Taryono Taryono; Endang Semiarti; Sismindari Sismindari (Journal of Tropical Life Science, 2014)
Glagah (Saccharum spontaneum L.) has potential value as a crop species and may also be used in sugarcane breeding programs; however, this germplasm has not been extensively used in breeding programs, primarily in relation to improve drought tolerance. The objectives of this experiment were to evaluate the effect of drought stress initiated at vegetative growth stage on growth, leaf proline content and protein pattern of seven glagah accessions (BOT-53, BOT-54, BOT-60, BOT-77, BOT-78, BOT-84, and BOT-88). The plants were propagated from single node stalk segments in polybag in the field under non-stress condition for two months. The two month-old plants were then subjected to drought stress by withholding watering for eight weeks. Untreated control plants were watered every two days. Results indicated that drought stress reduced plant height, stalk diameter and green leaf number. On the other hand, there was a little difference between drought-stressed and control plants in terms of proline content. The protein pattern showed that drought stress caused a change in gene expression in the form of induction or repression of protein expression. A specific protein with a low range of molecular weight (Rf value about 0.647) showed constitutively expressed in accession BOT-53 but drought-inducible expressed in BOT-54. Keywords: Drought stress, glagah, proline, protein pattern, Saccharum spontaneum